CTRP 9 mitigates the apoptosis and unfolded protein response of OGD/R-induced retinal ganglion cells by regulating the AMPK pathway - Yang, Xiaofan; Niu, Yuling (Polish Journal of Pathology, 2024)
C1q/TNF-related protein-9 (CTRP9) has been reported to play roles in several types of retinal diseases. However, the role and the potential mechanism of CTRP9 in glaucoma are still incompletely understood. The expression of CTRP9 in OGD/R-induced retinal ganglion cells (RGCs) was detected by quantitative real-time polymerase chain reaction and western blot assay. Cell proliferation was identified by cell counting Kit-8 assay. Flow cytometry, enzyme-linked immunosorbent assay and western blot assay were performed to assess cell apoptosis. Unfolded protein response (UPR), endoplasmic reticulum (ER) stress and the AMPK pathway were evaluated by western blot assay. The data showed that the expression of CTRP9 was significantly downregulated in OGD/R-induced 661W cells. OGD/R treatment reduced cell viability, promoted cell apoptosis and activated the UPR and ER stress. The overexpression of CTRP9 reversed the effects of OGD/R on 661W cell viability, apoptosis, the UPR and ER stress, as well as the AMPK pathway. However, Compound C, an inhibitor of AMPK signaling, reversed the protection of CTRP9 overexpression against injury from OGD/R in 661W cells. In summary, the results revealed that CTRP9 abated the apoptosis and UPR of OGD/R-induced RGCs by regulating the AMPK pathway, which may provide a promising target for the treatment of glaucoma.